2022
DOI: 10.21926/aeer.2202024
|View full text |Cite
|
Sign up to set email alerts
|

Soil Pollution Education: A Broad View of Knowledge on Soil Pollution and Educational Activities for Undergraduate Students

Abstract: Soil pollution is a major challenge for ensuring a healthy environment and for human health. One of the critical points in soil pollution policy is the education and public awareness of the problem caused by soil pollution. Education influences decision-making on soil and water care. It is crucial to spread knowledge to undergraduate and graduate students about the determinantal effects of soil pollution on ecosystems and humans, considering today’s students are tomorrow’s guardians of soil and human health. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In the specialized literature, it is strongly reported that contaminated soils have changes in their microbiological, chemical and physical properties, with repercussions on groundwater, aquifer systems and air quality. It is also common to find a significant association between soil, water, food and health since pollutants can accumulate at various levels in food chains and disrupt physiological or biological processes in several species [9][10][11][12]. The relevance of this correlation between soil and health is strongly present in the concept of "healthy soils", introduced by the European Union as an ambitious condition to be achieved by 2050 [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the specialized literature, it is strongly reported that contaminated soils have changes in their microbiological, chemical and physical properties, with repercussions on groundwater, aquifer systems and air quality. It is also common to find a significant association between soil, water, food and health since pollutants can accumulate at various levels in food chains and disrupt physiological or biological processes in several species [9][10][11][12]. The relevance of this correlation between soil and health is strongly present in the concept of "healthy soils", introduced by the European Union as an ambitious condition to be achieved by 2050 [13].…”
Section: Introductionmentioning
confidence: 99%